2018
DOI: 10.3389/fpsyt.2018.00497
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Sex, Personality Traits, Age of Onset and Disorder Duration to Behavioral Addictions

Abstract: Background and aims: Increases in the prevalence of behavioral addictions worldwide have led to a growth in the etiological research of the specific contribution of risk/protective factors to these disorders. The objective of this study was to assess the relative role of patients' sex, age of disorder onset and disorder duration on the clinical profile of behavioral addictions.Methods: Our sample included treatment-seeking patients diagnosed with gambling disorder (GD, n = 3,174), internet gambling disorder (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Most of the participants were men, coinciding with what has been reported in previous literature for sports betting (Granero et al, 2020). Being a man has been considered a risk factor for gambling behavior (Hing, Russell, Vitartas et al, 2016;Hing, Russell, Tolchard et al, 2016;Jim enez-Murcia et al, 2020;Kim, von Ranson, Hodgins, McGrath, & Tavares, 2018;Valero-Sol ıs et al, 2018). Our data supports this idea, emphasizing the weight of being a man in sports betting as a predictor for debts, as well as the direct relationship between being a man and the presence of worse economic harmful consequences, with an increase in the amount of debt accumulated and the highest bets per betting episode.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the participants were men, coinciding with what has been reported in previous literature for sports betting (Granero et al, 2020). Being a man has been considered a risk factor for gambling behavior (Hing, Russell, Vitartas et al, 2016;Hing, Russell, Tolchard et al, 2016;Jim enez-Murcia et al, 2020;Kim, von Ranson, Hodgins, McGrath, & Tavares, 2018;Valero-Sol ıs et al, 2018). Our data supports this idea, emphasizing the weight of being a man in sports betting as a predictor for debts, as well as the direct relationship between being a man and the presence of worse economic harmful consequences, with an increase in the amount of debt accumulated and the highest bets per betting episode.…”
Section: Discussionsupporting
confidence: 81%
“…A clear relationship between GD age of onset and GD severity has been previously reported 57 60 . Notably, the current paths by sex are partially in agreement with previous literature, reporting a strong relationship between gambling initiation, severity of the disorder, and age of onset for GD among males seeking treatment, compared to females 22 , 40 , 61 . However, in the current study, results showed that the relationship between GD onset age-GD severity is even stronger in females (magnitudes of − 0.38 vs − 0.28).…”
Section: Discussionsupporting
confidence: 90%
“…In this sense, with the growth of females participation in gambling activities 31 , sex appears as an increasingly important factor within the evaluation of aspects underlying severity of GD. In treatment-seeking individuals with GD, sex differences have been already reported 9 , 22 , 32 34 . However, very few studies evaluate the profile factors for gambling in females 18 , 35 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since available empirical evidence in the scientific literature has indicated that sex and age play an important moderating role in gambling ( Valero-Solís et al, 2018 ; Granero et al, 2020 ; Jiménez-Murcia et al, 2020 ), these two sociodemographic variables were considered.…”
Section: Introductionmentioning
confidence: 99%